Hubungan Efikasi Diri Dengan Kepatuhan Diet Rendah Garam Pada Lansia Hipertensi Di Pesisir Pantai Puskesmas Pakuhaji - Deswita, Reny; Syahroni; Elang Wibisana (Journal of Pubnursing Sciences, 2024)
Background: Hypertension is the number one risk factor for death globally, affecting more than one billion people. Hypertension does not cause any symptoms so it is called the silent killer. Mechanical hemodynamic changes, arterial stiffness, neurohormonal and autonomic dysregulation and decreased renal function increase the risk of hypertension in the elderly. Hypertension can be controlled by compliance with taking medication. Self-efficacy is a factor that plays an important role in treatment compliance. Objective: to determine the relationship between self-efficacy and adherence to a low salt diet in hypertensive elderly in the coastal area of ​​Pakuhaji Community Health Center. Method: Quantitative research with cross sectional design. A total of 84 respondents were drawn using purposive sampling technique. Inclusion criteria: respondent's age ≥ 60; Prolanis members at Pakuhaji Community Health Center; Able to communicate, read and write well. Time for research implementation March to July 2023. Data analysis using Spearman Rank. Results: There is a significant relationship between self-efficacy and low-salt diet compliance (p value 0.000), with a strong and positive correlation between self-efficacy and low-salt diet compliance (0.634). Conclusion: The higher the elderly's self-efficacy, the higher the adherence to a low-salt diet.